THE FRENCH LIEUTENANT’S WOMAN (1969) AND POSTMODERNISM - Nath, Lakhyajit (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this paper is to present a picture of literature under the influence of an age which culled literature as well as other aspects of society in a way which was undesirable as well as unpredictable. Literature is the mirror of society. Holding the finger of this well-known quote it can be remarked that literature reflects what has been going on in a particular society. Our prime concern here is to trace the influences of the postmodern era on the literature of that age, more specifically on John Fowles’ novel The French Lieutenant’s Woman (1969).